Transcriptome-Based Identification and Functional Characterization of NAC Transcription Factors Responsive to Drought Stress in Capsicum annuum L. - Borràs, Dionis; Barchi, Lorenzo; Schulz, Karina; Moglia, Andrea; Acquadro, Alberto; Kamranfar, Iman; Balazadeh, Salma; Lanteri, Sergio (Frontiers in Genetics, 2021)
Capsicum annuum L. is one of the most cultivated Solanaceae species, and in the open field, water limitation leading to drought stress affects its fruit quality, fruit setting, fruit size and ultimately yield. We identified stage-specific and a common core set of differentially expressed genes, following RNA-seq transcriptome analyses of a breeding line subjected to acute water stress followed by recovery (rewatering), at three stages of plant development. Among them, two NAC transcription factor (TF) genes, i.e. CaNAC072 and CaNAC104, were always upregulated after drought stress and downregulated after recovery. The two TF proteins were observed to be localized in the nucleus following their transient expression in Nicotiana benthamiana leaves. The expression of the two NACs was also induced by NaCl, polyethylene glycol (PEG) and abscisic acid (ABA) treatments, suggesting that CaNAC072 is an early, while CaNAC104 is a late abiotic stress-responsive gene. Virus-induced gene silencing (VIGS) of CaNAC104 did not affect the pepper plantlet´s tolerance to drought stress, while VIGS of CaNAC072 increased drought tolerance. Heterologous expression of CaNAC072 in Arabidopsis thaliana as well as in plants mutated for its homolog ANAC072 did not increase drought stress tolerance. This highlights a different role of the two NAC homologs in the two species. Here, we discuss the complex role of NACs as transcriptional switches in the response to drought stress in bell pepper.